The dialectic of practice and the logical structure of the tool : philosophy, archaeology and the anthropology of technology - Kozatsas, Jannis (Praehistorica mediterranea, 2020)
A critical review of recent trends in the archaeological and anthropological theory of technology from processual neo-positivism and postprocessual relativism to contemporary French and American anthropology, and the symmetrical theory of material culture.